Heterogeneity of environmental protection law’s impact on firms’ pollutant discharge - Li, Wenyu; Shan, Wei; Gao, Junguang (Frontiers in Environmental Science, 2023)
In 2015, China revised its Environmental Protection Law to strengthen regulations on firms’ pollution discharge. However, the efficacy of this law in protecting the environment remains unclear. By using panel data from China’s listed firms spanning from 2010 to 2020, this paper applies the continuous difference model to analyze the impact of the Environmental Protection Laws on firms’ pollutant emissions. The results demonstrate a significant and consistent reduction in both total pollutant emissions and pollutant emissions per firm’s outcome due to the implementation of the Environmental Protection Laws. Additionally, the study indicates a significant reduction in pollutant emissions among firms that did not receive environmental protection subsidies, state-owned firms, and firms without prior environmental pollution behaviors. The findings also suggest a two-year lag time for the Environmental Protection Law to impact firms’ pollution emissions per outcome. These results carry important practical implications for the government’s efforts to transform environmental protection policies and for firms seeking to enhance their environmental performance.